PHYLOSOPHICAL AND CONSTITUSIONAL PROTECTION TOWARDS RELIGION IN INDONESIA - Silfiah, Rossa Ilma; Luth, Thohir; Sugiri, Bambang; Aprilianda, Nurini (Brawijaya Law Journal, 2016)
Legal protection on religion is certainty for a state with Pancasila principle. The first principle    the Divinity of the Only God has been spirit of the following points, as living guidance for Indonesian country.  The believing of    the Divinity of the Only God shows that the Indonesian Republic is religious based country by protecting freedom to have religion for its people.  This regulation has implication in governmental circle, that the country makes Religion Ministry as one of ministries that its existence has the same position to other state institutions.   The implementation of legal protection toward religion needs legitimating in the field of civil law, showed in issuing President   Decree   No. 1 of 1965 on the Preventing of    Misuse and/or Religion Staining. The existence of this   Decree  in Old Order has been legitimated  newly as a Law  by issuing the Law   No. 5 of 1969, thus the  President Decree has been added to the  Criminal Code, Act   156a.